Pengembangan bahan ajar matematika berbasis diferensiasi konten untuk peserta didik kelas IV sekolah dasar - Vivi Novatona; Riyadi Riyadi; Tri Budiharto (Didaktika Dwija Indria, 2023)
This study aims to determine the process and results of the development of valid and practical mathematics teaching materials. This study uses the 4D model research and development method (Define, Design, Development, and Disseminate) by Thiagarijan. This research is only limited to the third stage, namely Development. Source of data in this research includes teachers of Class IV SD Negeri Karangasem IV Surakarta, material experts, media experts, and linguists. The result of this research is the development of valid and practical learning media obtained through the assessment of the validators. Material expert validators scored 86.9%, media experts 90,3%, and linguists 100%. While practicality is obtained from the assessment of teachers and students. Teacher assessment obtained a score of 90,5% and students 87,1%.